Distribution of transpulmonary pressure during one-lung ventilation in pigs at different body positions - Wittenstein, Jakob; Scharffenberg, Martin; Yang, Xiuli; Bluth, Thomas; Kiss, Thomas; Schultz, Marcus J.; Rocco, Patricia R. M.; Pelosi, Paolo; Gama de Abreu, Marcelo; Huhle, Robert (Frontiers in Physiology, 2023)
Background Global and regional transpulmonary pressure (PL) during one-lung ventilation (OLV) is poorly characterized. We hypothesized that global and regional PL and driving PL (ΔPL) increase during protective low tidal volume OLV compared to two-lung ventilation (TLV), and vary with body position.In sixteen anesthetized juvenile pigs, intra-pleural pressure sensors were placed in ventral, dorsal, and caudal zones of the left hemithorax by video-assisted thoracoscopy. A right thoracotomy was performed and lipopolysaccharide administered intravenously to mimic the inflammatory response due to thoracic surgery. Animals were ventilated in a volume-controlled mode with a tidal volume (VT) of 6 ml kg −1 during TLV and of 5 ml kg −1 during OLV and a positive end-expiratory pressure (PEEP) of 5 cmH2O. Global and local transpulmonary pressures were calculated. Lung instability was defined as end-expiratory PL<2.9 cmH2O according to previous investigations. Variables were acquired during TLV (TLVsupine), left lung ventilation in supine (OLVsupine), semilateral (OLVsemilateral), lateral (OLVlateral) and prone (OLVprone) positions randomized according to Latin-square sequence. Effects of position were tested using repeated measures ANOVA.End-expiratory PL and ΔPL were higher during OLVsupine than TLVsupine. During OLV, regional end-inspiratory PL and ΔPL did not differ significantly among body positions. Yet, end-expiratory PL was lower in semilateral (ventral: 4.8 ± 2.9 cmH2O; caudal: 3.1 ± 2.6 cmH2O) and lateral (ventral: 1.9 ± 3.3 cmH2O; caudal: 2.7 ± 1.7 cmH2O) compared to supine (ventral: 4.8 ± 2.9 cmH2O; caudal: 3.1 ± 2.6 cmH2O) and prone position (ventral: 1.7 ± 2.5 cmH2O; caudal: 3.3 ± 1.6 cmH2O), mainly in ventral (P≤0.001) and caudal (P=0.007) regions. Lung instability was detected more often in semilateral (26 out of 48 measurements; P=0.012) and lateral (29 out of 48 measurements, P<0.001) as compared to supine position (15 out of 48 measurements), and more often in lateral as compared to prone position (19 out of 48 measurements, P=0.027).Compared to TLV, OLV increased lung stress. Body position did not affect stress of the ventilated lung during OLV, but lung stability was lowest in semilateral and lateral decubitus position.